2015
DOI: 10.5742/meaa.2015.92609
|View full text |Cite
|
Sign up to set email alerts
|

Health Profile of Elderly Patients Registered in the Elderly Home Based Primary Care , Dubai , United Arab Emirates

Abstract: Introduction: The proportion of the elderly population in the United Arab Emirates is constantly growing. The aging population presents a challenge for the public healthcare system. Accurate health data is required both from an epidemiological and strategic health care planning perspective. Objectives: To estimate the prevalence of disease, impairment and disability among the elderly. Methodology: A retrospective study was carried out and records of comprehensive assessment forms of elderly patients aged 60 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 14 publications
2
14
1
1
Order By: Relevance
“…It's more prevalent in females than males (29.0% and 11.1%) respectively (P<0.05). These findings agreed with other study in UAI, showed the prevalence among elderlies (25.9% in females and 10.4% in males) [24]. And it also agreed with Hassan SK study which revealed that, 2.2% of females and 0.8% of males had the disease [12].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…It's more prevalent in females than males (29.0% and 11.1%) respectively (P<0.05). These findings agreed with other study in UAI, showed the prevalence among elderlies (25.9% in females and 10.4% in males) [24]. And it also agreed with Hassan SK study which revealed that, 2.2% of females and 0.8% of males had the disease [12].…”
Section: Discussionsupporting
confidence: 81%
“…While Abolfotouh et al showed (4.6%). Another study was conducted in Dubai, United Arab Emirates showed that 38.3% of the elderly patients had depression [24].…”
mentioning
confidence: 99%
“…On a global scale, according to the United Nations, by mid-century, the number of people over 60 years will represent 32% of the world population [ 1 ]. Considering the UAE, the proportion of elderly persons aged 60 years and above in the year 2000 was 5.1% and is expected to increase to 23.6% by 2025 [ 2 ]. The UAE provides a unique population in which the UAE nationals make up 11.6% of the population while the other 88.4% are expatriates [ 3 ], many of whom have been born in the UAE or have lived there for generations.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it provides a controlled environment in which we can study both UAE nationals and expatriates. This, in addition to the rise in life expectancy from 74 years to 78 years [ 2 ], means there is an increased need to address age-related chronic diseases within the UAE.…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of the elderly population is growing much faster than the overall population due to decreasing fertility and increasing life expectancy. 1 In Indian society the increasing number of older people has been well perceived. Though increase in ageing population represents the success of socioeconomic development and good public health practice, it has also lead to economic and social crisis due to increased demand for health and welfare services.…”
Section: Introductionmentioning
confidence: 99%